2011
DOI: 10.1007/s11069-011-9885-6
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerability of the European air traffic network to spatial hazards

Abstract: The 2010 eruption of the Eyjafjallajökull volcano had a devastating effect on the European air traffic network, preventing air travel throughout most of Europe for 6 days (Oroian in ProEnvironment 3:5-8, 2010). The severity of the disruption was surprising as previous research suggests that this type of network should be tolerant to random hazard [378][379][380][381][382] 2000). In this paper, we demonstrate that the ash cloud was unexpectedly disruptive because it was spatially coherent rather than uniformly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
100
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 17 publications
0
100
0
1
Order By: Relevance
“…In the short term and most obviously, aerosol particles can degrade visibility and damage aviation and transport (Wilkinson et al, 2012;Prata and Tupper, 2009). The World Health Organization (WHO), which has reported country estimates of air pollution exposure and its health impact (WHO, 2016), has suggested that 6.5 million deaths (11.6 % of all global deaths) may be associated with indoor or outdoor air pollution, and 92 % of the world's population lives in places where air quality levels do not meet the WHO Ambient Air quality guideline of an annual mean PM 2.5 (particulate matter with a diameter of less than 2.5 µm) concentration of less than 10 µg m −3 .…”
Section: Introductionmentioning
confidence: 99%
“…In the short term and most obviously, aerosol particles can degrade visibility and damage aviation and transport (Wilkinson et al, 2012;Prata and Tupper, 2009). The World Health Organization (WHO), which has reported country estimates of air pollution exposure and its health impact (WHO, 2016), has suggested that 6.5 million deaths (11.6 % of all global deaths) may be associated with indoor or outdoor air pollution, and 92 % of the world's population lives in places where air quality levels do not meet the WHO Ambient Air quality guideline of an annual mean PM 2.5 (particulate matter with a diameter of less than 2.5 µm) concentration of less than 10 µg m −3 .…”
Section: Introductionmentioning
confidence: 99%
“…While the design of infrastructure networks has been of interest to geographers since the 1960s [12], [13], spatial network design has emerged only more recently as an area of scientific research [14]. Many applications of spatial network analysis focus on traffic or transportation networks [15], [14], [16], [17], [18] or physical infrastructures that deliver information, such as the internet or mobile telephony [14], [19]. Others find that the constraints of geographic space can dramatically change the implications found in abstract network models [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…The first is how the cost of adding edges or otherwise connecting nodes in space influences network structure and design choices [14], [23]. The second strand uses known or theoretical spatial properties of networks to understand their performance in the case of attacks, failures or other contingency events [6], [18], [24].…”
Section: Introductionmentioning
confidence: 99%
“…The World Airline Network is a coreperiphery network [2] with long-range connections that make possible its relatively small diameter compared to its size. The existence of central hubs that form the interconnected core, together with the long-range connections that separate the hubs to span across the globe, gives the WAN its unique topology [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%